IMPLEMENTASI METODE PEMBELAJARAN BAHASA ARAB BERBASIS MULTIPLE INTELLIGENCE PADA SISWA KELAS VII MTS HASAN MUNADI - Fanani, Mochammad; Taubah, Miftachul (Universitas Muhammadiyah Mataram, 2024)
MTs Hasan Munadi is one of the schools that implements the implementation of the Arabic language learning method based on multiple intelligences for class VII students. This study aims to determine the implementation of the Arabic language learning method based on multiple intelligences in class VII students of MTs Hasan Munadi and to determine the supporting and inhibiting factors. This study uses a qualitative research method with a type of field research. The data collection techniques through observation, interviews and documentation. While the data analysis technique uses descriptive analysis techniques. From the results of the study it can be concluded that: 1) Learning Arabic in class VIII MTs Hasan Munadi uses a multiple intelligence-based learning method. In its application, learning consists of activities; preliminary activities, core activities and closing activities. In the core activities, the teacher carries out various strategies, such as asking students to repeat the readings read by the teacher, asking them to have conversations, watching videos in Arabic and conducting learning outside the classroom. 2) the supporting factor is the use of varied learning methods. The inhibiting factor is that the teacher must be more patient and patient in teaching students. Keywords Arabic Learning, Methods, Multiple Intelligence.